The Role of Metacognitive Scaffolding in Mathematical Communication on Mathematics Students - Damar Rais; Yue Wen Yan; Muhammad Kashif (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although written mathematical communication is central to students’ ability to express reasoning coherently, the role of metacognitive scaffolding in connecting internal thinking with external mathematical discourse remains insufficiently examined. This study investigates whether metacognitive scaffolding functions as a bridge between internal thought and external discourse in students’ written mathematical communication and whether initial metacognitive awareness moderates this effect. A quasi-experimental pretest–posttest control group design was employed with 72 mathematics education students. The experimental group received six sessions of metacognitive scaffolding through guided prompts, such as “What is your first step and why?” and “How does this step connect to the next?”, whereas the control group received conventional instruction without such prompts. Written mathematical communication was assessed using a validated test measuring structural coherence, including logical flow, mathematical language use, and step-linking. Metacognitive awareness was measured using an adapted Metacognitive Awareness Inventory questionnaire. The ANCOVA results revealed a significant and large effect of metacognitive scaffolding on structural coherence, ηp² = 0.292, p < .001, with the strongest effects observed in logical flow and step-linking. Metacognitive awareness also significantly moderated the intervention effect, B = -3.41, p = .009, indicating that students with lower initial metacognitive awareness benefited most from the intervention. Qualitative think-aloud protocols further showed that scaffolding activated internal discourse, promoted the use of logical connectors, and strengthened self-monitoring during written mathematical explanation. These findings contribute to commognitive theory by demonstrating that improving external mathematical communication can support internal cognitive processes. Practically, the study suggests that mathematics educators can integrate metacognitive prompts into worksheets to help students produce more coherent written explanations, particularly those with underdeveloped metacognitive skills.